Tranexamic acid as a therapeutic option for melasma management: meta-analysis and systematic review of randomized controlled trials - Retaj Calacattawi; Mohammed Alshahrani; Maryam Aleid; Fatimah Aleid; Khalid Basamih; Ghada Alsugair; Raghad Alqahtani; Noor AlKhabbaz; Yaser Algaidi; Latifa Alrakayan; Abdulaziz Almohanna; Afnan Madkhali; et al. (Journal of Dermatological Treatment)
Purpose: This study aimed to evaluate the efficacy of tranexamic acid (TXA) in treating melasma through a meta-analysis and systematic review of randomized controlled trials (RCTs). The study focused on identifying associated adverse effects and comparing TXA’s effectiveness with other melasma treatments.Materials and methods: Following PROSPERO and PRISMA guidelines, an extensive electronic search was conducted across four databases for RCTs on TXA use in melasma. Inclusion criteria encompassed full-text English articles with specific outcome measures, while studies with high bias risk or non-English publications were excluded. Data were extracted from 22 relevant studies and analyzed using the RevMan software, with heterogeneity identified using I² statistics and forest plots.Results: A total of 22 studies with 1280 patients were included. TXA was administered orally, topically, or via injection, with treatment durations ranging from 8 weeks to nearly 2 years. TXA significantly reduced melasma severity, evidenced by reductions in MASI, mMASI, MI, and hemi-MASI scores. Oral TXA showed the most substantial decrease in MASI scores, followed by injections and topical applications. However, studies exhibited high heterogeneity, particularly in combined treatments. Adverse effects included gastrointestinal discomfort, skin irritation, and menstrual irregularities.Conclusions: TXA is effective in treating melasma, either alone or combined with other treatments. Despite significant reductions in melasma severity, further research is necessary to standardize TXA administration methods and address long-term effects. The high heterogeneity observed suggests a need for more consistent treatment protocols.